1935
DOI: 10.1021/j150363a001
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Theory of Surface Conductivity at Solid-Liquid Interfaces

Abstract: The double layer theory of Otto Stern may be briefly summarized as follows (7, 12,14). The theory of Helmholtz gives values for the capacity of the double layer which agree approximately with those obtained from electrocapillary experiments. However, owing to kinetic heat motion, the double layer ions facing the liquid cannot have the distribution postulated by Helmholtz. On the other hand, Gouy's (6) theory, which is based on the existence of a diffuse double layer, gives values for the capacity which are far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1936
1936
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 7 publications
3
18
0
Order By: Relevance
“…The EDL contains more ions than the bulk, which results in a surface conductance due to their motion in the electric field ͑Urban et al., 1934;Kittaka and Morimoto, 1976͒, and this conductance can be measured in an ac field at sufficiently high frequency. Such conductance measurements can also be performed in a dc field, but the electro-osmotic contributions ͑see Sec.…”
Section: Surface Conductancementioning
confidence: 99%
“…The EDL contains more ions than the bulk, which results in a surface conductance due to their motion in the electric field ͑Urban et al., 1934;Kittaka and Morimoto, 1976͒, and this conductance can be measured in an ac field at sufficiently high frequency. Such conductance measurements can also be performed in a dc field, but the electro-osmotic contributions ͑see Sec.…”
Section: Surface Conductancementioning
confidence: 99%
“…Bikerman (1942) suggested that materials such as clays, which are capable of swelling in aqueous media, form a gel la3,er on the surface that is conductive but electrokinetically inactive. Other theories have suggested mobility of ions in the Stern layer (Urban et al, 1935) and conduction by ionizable surface hydroxyl groups (Holmes et al, 1965). These ideas are not mutually exclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Urban, White, and Strassner (1935) also state that the ,con Srnoluchowski conductance of pyrex glass is very slight at 1000 cycles. It is not possible, however, to choose between a normal and a tangential conductance explanation of the data on suspended cells.…”
Section: Discussionmentioning
confidence: 87%